Profiles in female poverty: a study of five poor working women in Kerala - Gulati, Leela (Delhi, 1981)
In this book, economist-ethnographer Leela Gulati has assembled the life histories of five women who belong to the bottom of the caste pyramid in Kerala, which is one of India's poorest and most densely populated states. These intimate and poignant sketches are based on intensive interviews and close rapport between the author and her respondents. They reveal with unprecedented clarity and dramatic impact the way in which the underprivileged women of Kerala are dominated by the relentless necessity of selling their bodies for the energy in their muscles and the load-bearing capacity of their backs and necks. The physical and psychic burdens endu red by these women as a normal part of life, seem intolerable espe cially in view of their frail build and meagre diet. Yet as one reads Leela Gulati's book, it is clear that the women involved are remarkably free of self-pity, however much they are entitled to it, and that they are determined to cope with their situation not with fatalistic resignation, but literally with every calorie they can get from the food they eat. One ends each case, therefore, admiring as much as feeling sorry for the five principal figures.
Keywords: Poverty